Do no-loan policies change the matriculation patterns of low income students? - Glen R. Waddell; Larry D. Singell (Institute for the Study of Labor (IZA), 2009)
We empirically examine whether there is discernable variation in the matriculation patterns of low-income students at public flagship institutions in the United States around changes in institutional financial-aid policies that target resident, low-income students with need-based aid. While enrollment responses cannot be attributed to these programs, we do find that institutions that introduce income-targeted aid subsequently enroll financially needier and geographically more-distant students. These findings imply that improved access may actually displace some needy students in favor of others.
urn:nbn:de:101:1-2009092820
Keywords: I23; I21; J24; 330; Low income; financial aid; no loan; Pell; Studierende; Niedrigeinkommen; Bildungsverhalten; Studienfinanzierung; USA